2016
DOI: 10.1111/odi.12450
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS in women and children in India

Abstract: Management of HIV in India has significantly improved with many international and local programmes supporting prevention and treatment. However, there are areas in India where women and children living with HIV endure a myriad of medical, psychological and social challenges. Women in rural poor areas in India have little control over important aspects of their life. Often, they have little decision‐making powers within their families on matters that affect them personally. They find themselves unable to negoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…4 It is also estimated that the 2.5 million people living with HIV/AIDS in India, of which nearly 40% were women. 5 The dramatic increase of the HIV infection among the women is due to the biological vulnerabilities, poor socioeconomic states, and dominant sexual practice of males. The other cause of the HIV infection among the women is transmission of HIV infection from the male partners having risky sexual behavior during occupational migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It is also estimated that the 2.5 million people living with HIV/AIDS in India, of which nearly 40% were women. 5 The dramatic increase of the HIV infection among the women is due to the biological vulnerabilities, poor socioeconomic states, and dominant sexual practice of males. The other cause of the HIV infection among the women is transmission of HIV infection from the male partners having risky sexual behavior during occupational migration.…”
Section: Introductionmentioning
confidence: 99%
“…The other cause of the HIV infection among the women is transmission of HIV infection from the male partners having risky sexual behavior during occupational migration. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Though research thus far has indicated high HIV prevalence rates among sex workers, long distance truck drivers, men having sex with men, and injection drug users, married women are increasingly at high risk (Mothi, Lala, & Tappuni, 2016). The majority of new HIV cases in India – 87% – are a result of heterosexual contact (Mothi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of new HIV cases in India – 87% – are a result of heterosexual contact (Mothi et al, 2016). However, routes of transmission for heterosexual men and women are distinct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation